Does the Microbiome Affect the Outcome of Renal Transplantation? - Campbell, Paul M.; Humphreys, Gavin J.; Summers, Angela M.; Konkel, Joanne E.; Knight, Christopher G.; Augustine, Titus; McBain, Andrew J. (Frontiers in Cellular and Infection Microbiology, 2020)
It has become increasingly clear that the human microbiome is tightly entwined with human health, and emerging evidence suggests that the microbiome is affected by solid organ transplantation. Kidney transplantation is the gold standard treatment for End-Stage Renal Disease (ESRD), the advanced stage of Chronic Kidney Disease (CKD). The question of how ESRD and transplantation affect the microbiome and vice versa has several key aspects, including: how the microbiome is affected by the increased concentrations of toxins such as urea and creatinine, (which are elevated in ESRD), whether restoration of renal function following transplantation impacts on the composition of the microbiome, and the impact of lifelong administration of immunosuppressive drugs on the microbiome. Changes in microbiome composition and activity have been reported in ESRD and in therapeutic immunosuppression, but how these changes affect outcome of transplantation is not well understood. Here, we consider the current evidence that changes in kidney function and immunosuppression following transplantation impact on the oral, gut, and urinary microbiomes in kidney transplant patients. The potential for these microbiomes to lead to disease, systemic inflammation, or rejection of the organ itself is then discussed, along with the possibility that restoration of kidney function might re-establish orthobiosis.